Effect of use of MWCNT/oil nanofluid on the performance of solar organic Rankine cycle - Alireza Refiei; Reyhaneh Loni; G. Najafi; A.Z. Sahin; Evangelos Bellos (Energy Reports, 2020)
In the current study, a solar-driven organic Rankine cycle (ORC) system was thermodynamically, economically and environmentally investigated. A focal point concentrator with two different cavity-shape receivers was investigated as the ORC heat source. More specifically, the cylindrical and the hemispherical cavity receivers were examined and compared as the most usual and promising choices. MWCNT/oil nanofluid and R113 were used as the solar heat transfer fluid and ORC working fluid respectively. The main aim of this research is an investigation of different cavities in the solar dish and the investigation of the impact of the use of nanofluids in the solar system by different points of view. The results of this work showed that the hemispherical cavity receiver with nanofluid is the most efficient choice with 21.4% system efficiency, while the use of pure thermal oil in the hemispherical cavity leads to 18.9%. On the other hand, the use of the cylindrical cavity leads to 17.8% and 15.8% system efficiency with nanofluid and pure thermal oil respectively. The levelized cost of electricity (LCOE) was 0.077 exteuro/kWh and 0.076 exteuro/kWh for the cylindrical and hemispherical cavity receiver respectively. Moreover, it was concluded that the solar ORC system with the hemispherical cavity receiver as the ORC heat source had resulted in more positive environmental influence related to the cylindrical one.
Keywords: 330; Solar ORC system; MWCNT/oil nanofluid; Cavity receivers; Economic analyses; Environmental analyses